PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUASAN WISATAWAN JAWA TIMUR PARK II KOTA BATU - Sari, Fitri Wulan; anto, Subi (Jurnal Ilmiah Mahasiswa FEB, 2013)
The development of tourism today is very fast and provide opportunity for national and regional economic growth. For  the development of  tourism and the government  has  continued to be driven  belief that  tourism  can  become  the leading sectors  replace oil and natural gas  that has been the  foundation of  the government  in supporting the  state revenue. To that end, various  regions  in Indonesia are competing to develop the tourism sector in order to raise revenues. Marketing concepts evolve with  the needs of  the community. One of the primary needs  to be taken by  the manufacturer  is  the need for services. In  marketing activities, important thing to note is how the providers of such services marketing mix that attention can then measure the satisfaction of its customers.Keywords: Product, Price, Place, Promotion, Physical Evidence, People,  Process, Tourist Satisfaction